Faktor yang Mempegaruhi Perilaku Peralihan Pelanggan: Peran Mediasi Kepuasan dan Kepercayaan Pelanggan - Muthmainah; Cholil, Muhammad (Jurnal Riset Bisnis dan Investasi, 2021)
This study aims to examine and discuss the factors that influence customer switching behavior to other products and/or institutions with respondents consisting of customers of Islamic banks in the Surakarta area using the convenience sampling technique. The results are: (1) there is a positive effect between service quality on customer satisfaction and customer trust, between religiosity on customer trust, between customer experience on customer satisfaction and customer trust; (2) customer satisfaction has a negative effect on customer switching behavior; (3) a mediating role of customer satisfaction on the effect of service quality and customer switching behavior. Whatever the outcome, managers and/or employees must periodically expand their efforts to achieve customer satisfaction and customer trust through increased service quality excellence, sharia value conformity, and the excellent customer experience to anticipate possible customer switching behavior. The theoretical and practical implications, as well as the limitations of research, will be later discussed.